2022
DOI: 10.1093/mnras/stac3401
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional numerical simulations of structured gamma-ray burst jets

Abstract: After the detection of GRB 170817A, the first unambiguous off-axis gamma-ray burst (GRB), several studies tried to understand the structure of GRB jets. The initial jet structure (directly produced by the central engine) can be partially preserved, or can be completely modified by the interaction with the environment. In this study, we perform three-dimensional, special relativistic hydrodynamics simulations of long GRB jets evolving through a massive progenitor star. Different jet scenarios were considered: T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 72 publications
0
6
0
Order By: Relevance
“…For simplicity, we assume an initial top-hat structure for the jet as launched by the central engine. This is reasonable considering that any initial complex jet structure (e.g., Gaussian) is expected to converge to a top-hat structure as the jet will strongly be collimated during its propagation across the dense medium (e.g., see Urrutia et al 2023). It should be noted that this is not inconsistent with observations of GW170817/GRB 170817A, as the more complex "structured jet" is expected to emerge after the jet breakout (also see §2.3.2).…”
Section: Initial Conditions: the Jetmentioning
confidence: 91%
“…For simplicity, we assume an initial top-hat structure for the jet as launched by the central engine. This is reasonable considering that any initial complex jet structure (e.g., Gaussian) is expected to converge to a top-hat structure as the jet will strongly be collimated during its propagation across the dense medium (e.g., see Urrutia et al 2023). It should be noted that this is not inconsistent with observations of GW170817/GRB 170817A, as the more complex "structured jet" is expected to emerge after the jet breakout (also see §2.3.2).…”
Section: Initial Conditions: the Jetmentioning
confidence: 91%
“…For simplicity, we assume an initial top-hat structure for the jet as launched by the central engine. This is reasonable considering that any initial complex jet structure (e.g., Gaussian) is expected to converge to a top-hat structure as the jet will strongly be collimated during its propagation across the dense medium (see, e.g., Urrutia et al 2023). It should be noted that this is not inconsistent with observations of GW170817/GRB 170817A, as a more complex structured jet is expected to emerge after the jet breakout (also see Section 2.3.2).…”
Section: Initial Conditions: the Jetmentioning
confidence: 91%
“…In reality, after the breakout, there is a complex jet structure, composed of a jet core and the cocoon in the wings (Mizuta & Ioka 2013;Lamb & Kobayashi 2017;Lazzati et al 2017;Lamb & Kobayashi 2018;Lazzati et al 2018;Gottlieb et al 2021). However, it has been shown that the jet core can be approximated to have a top-hat structure, and its opening angle is comparable to θ 0 at sufficiently late times after the breakout (Gottlieb et al 2021;Urrutia et al 2023 for prompt jets). Hence, here, with the jet opening angle θ j ∼ θ 0 we refer to the jet core structure.…”
Section: Jet Opening Anglementioning
confidence: 99%
“…There are some fundamental differences between the JJEM and many papers that study jet-driven explosions that operate only for rapidly rotating pre-collapse cores and therefore the jets that the newly born NS or BH launch have a fixed axis (e.g., Khokhlov et al 1999;Aloy et al 2000;MacFadyen et al 2001;Maeda et al 2012;López-Cámara et al 2013;Bromberg & Tchekhovskoy 2016;Nishimura et al 2017;Wang et al 2019;Grimmett et al 2021;Perley et al 2021;Gottlieb et al 2022;Obergaulinger & Reichert 2023;Urrutia et al 2023). These differences are as follows (e.g., Soker 2022c).…”
Section: Introductionmentioning
confidence: 99%